Survival of full versus partial acquisitions : The moderating role of firm's internationalization experience, cultural distance, and host country context characteristics - Wang, Yi; Larimo, Jorma (Elsevier, 2020)
The high divestment rates of acquired foreign units indicate challenges connected to planning and management of foreign acquisitions. In this paper we analyze the moderating effect of internal and external variables on the relationship between acquirers’ ownership strategy and survival of acquired foreign units. We test our hypotheses on a sample of 1275 acquisitions conducted by Finnish firms in various countries during the period 1980–2005. The results indicate that the probability of survival does not differ significantly between full and partial acquisitions. We further find that the likelihood of survival in full, relative to partial acquisitions, is positively associated with the acquisition-specific experience, but inversely related to general international and target country experience. The results also reveal that the positive impact of full acquisitions is stronger if the acquisitions are made in culturally similar countries, in less developed economies, and in markets where the country risk has increased after entry.
Keywords: Foreign direct investments; Foreign acquisitions; Survival of foreign acquired units; Full and partial acquisitions; Finland; fi=Kansainvälinen liiketoiminta|en=International Business|